Clinical Comparison of Sinus Lift via Summers Osteotomy and Piezosurgery - Mehrdad Radvar; Majid Reza Mokhtari; Sara Vaezi; Anahita Shahi (Mashhad University of Medical Sciences, 2017)
Introduction: Sinus lift is a process that could be performed by two methods. In the closed sinus lift, hybrid materials enter a suitable position through a created cavity. Afterwards, the materials are pressed without damaging the sinus membrane, and the implants are usually placed at the same time. Closed sinus lift is carried out via osteotomy and piezosurgery, and each of the techniques has certain advantages and limitations. The present study aimed to compare the clinical results of closed sinus lift using the summers osteotomy and piezosurgery. Materials and Methods: In this study, 20 patients requiring dental implants in the posterior segment of the maxilla via sinus lift surgery were randomly divided into two groups. The first group received piezosurgery, and the second group underwent summers osteotomy for sinus lift. Postoperative Schneiderian membrane perforation, inflammation, pain, bone gain, and bone loss were compared between the groups six months after the surgery using Mann-Whitney U test and two-sample t-test. Results: In the groups receiving piezosurgery and summers osteotomy, mean sinus lift was 3.6±0.9 and 4.0±2.2 mm, pain score was 1.1±1.2 and 0.9±0.8, bone gain was 2.2±0.8 and 3.1±1.3 mm, and crestal bone loss was 1.1±1.2 and 0.9±0.8 mm, respectively. Moreover, no Schneiderian membrane perforation was observed in the two methods, and the differences between the groups were not considered significant (P>0.05). Conclusion: According to the results, the clinical outcomes of piezosurgery in sinus lift are similar to those of summers osteotomy. Therefore, piezosurgery could be a proper alternative to summers osteotomy in sinus lift surgery.